2014
DOI: 10.1007/s11199-014-0437-x
|View full text |Cite
|
Sign up to set email alerts
|

“She” and “He” in News Media Messages: Pronoun Use Reflects Gender Biases in Semantic Contexts

Abstract: Previous research has shown a male bias in the media. This study tests this statement by examining how the pronouns She and He are used in a news media context. More specifically, the study tests whether He occurs more often and in more positive semantic contexts than She, as well as whether She is associated with more stereotypically and essential labels than He is. Latent semantic analysis (LSA) was applied to 400 000 Reuters' news messages, written in English, published in 1996-1997. LSA is a completely dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 50 publications
1
13
0
Order By: Relevance
“…Altogether, participants reproduced gender stereotype content by combining female-dominated occupations more often with communal than agentic traits and male-dominated occupations more often with agentic than communal traits (Studies 1 through 3), female-definitional nouns/pronouns more often with communal than agentic traits, and male-definitional nouns/pronouns more often with agentic than communal traits (Studies 1 and 2). These findings are consistent with research showing that women and men were presented gender stereotypically in the media (Gustafsson Sendén, Sikström, & Lindholm, 2015; Lauzen, Dozier, & Horan, 2008; Matud, Rodrigez, & Espinosa, 2011; Signorielli & Kahlenberg, 2001) and in recommendation letters (Madera, Hebl, & Martin, 2009). Also, experimental studies have found that female- or male-dominated occupations increased the accessibility of gender-stereotypically congruent pronouns and traits (Blair & Banaji, 1996; Kreiner, Sturt, & Garrod, 2008).…”
Section: Discussionsupporting
confidence: 91%
“…Altogether, participants reproduced gender stereotype content by combining female-dominated occupations more often with communal than agentic traits and male-dominated occupations more often with agentic than communal traits (Studies 1 through 3), female-definitional nouns/pronouns more often with communal than agentic traits, and male-definitional nouns/pronouns more often with agentic than communal traits (Studies 1 and 2). These findings are consistent with research showing that women and men were presented gender stereotypically in the media (Gustafsson Sendén, Sikström, & Lindholm, 2015; Lauzen, Dozier, & Horan, 2008; Matud, Rodrigez, & Espinosa, 2011; Signorielli & Kahlenberg, 2001) and in recommendation letters (Madera, Hebl, & Martin, 2009). Also, experimental studies have found that female- or male-dominated occupations increased the accessibility of gender-stereotypically congruent pronouns and traits (Blair & Banaji, 1996; Kreiner, Sturt, & Garrod, 2008).…”
Section: Discussionsupporting
confidence: 91%
“…Recently, text analysis started to play a significant role in psychological research (e.g., Eichstaedt et al, 2015;Gustafsson Send en et al, 2014;Mooijman, Hoover, Lin, Ji, & Dehghani, 2018;Van Swol & Kane, 2018), for instance, in reliably evaluating an individual's personality, status, or mood just based on the use of pronouns (see Campbell & Pennebaker, 2003;Pennebaker, 2011). Thus, analyzing 400,000 articles (a dataset released by Reuters for research and the development of natural language processing) would take 400,000 hours, which would require 200 full-time coders working for a year if every article were analyzed for an hour (based on 2,000 working hours per year; for details see Gustafsson Send en, Sikstr€ om, & Lindholm, 2015). As such, our work facilitates the study of agency and communion in more accessible and sizable datasets (e.g.…”
Section: Future Researchmentioning
confidence: 99%
“…Moreover, words associated with She-contexts included more words denoting gender, and were more homogeneous than the words associated with He-contexts. Altogether, these results indicate that men are represented as the norm in these media [17].…”
Section: Review Of Literaturementioning
confidence: 59%